Birds of the National Sanctuary Tabaconas Namballe, eastern slope of the Peruvian Northern Andes - Salazar, Sonia (2018)
The Tabaconas Namballe National Sanctuary (TNNS) is located at the limit of distribution of many endemic species from the Northern Andes, in an area threatened by deforestation and with many gaps in ornithological information. We report an updated list of species of the Sanctuary, and identify those species of conservation concern. We sampled three representative sites: Páramos, Chichilapa and El Sauce, during the dry season (September - October in 2014) and rainy season (March - April in 2015). We employed several complementary methods: counting points, mist-nets, nocturnal transects and non-systematic records. We recorded 197 (40 families) and 153 (39 families) species in the dry and rainy seasons respectively, with a total of 226 species and 42 families. In order to get an updated checklist, we include records of an average of 45 trap cameras, operative from August 2014 to April 2015, and we compile conclusive records from previous ornithological assessments. This work reports 82 new records of birds of the Sanctuary, 7 of which come from camera traps. In this way, the bird diversity of the Sanctuary is 290 species and 46 families. In addition to the 45 species between endemic, threatened and near threatened with extinction, we highlight a new record from the region Cajamarca, the Gray Tinamou Tinamus tao. Our results suggest that there is still much to know about the diversity of birds in the Sanctuary, however, it highlights the key role of this protected area in terms of bird conservation in this region.